Foliar absorption and root translocation of nitrogen from different chemical forms in seedlings of two Mediterranean trees - Uscola, Mercedes; Villar-Salvador, Pedro; Oliet, Juan; Warren, Charles R (Environmental and Experimental Botany, 2014)
Along with root uptake, plants can also absorb N through leaves. There are few comparative studies on the foliar absorption of N from different chemical forms of N in forest tree species. We compared the foliar N absorption capacity in seedlings of two forest trees widespread in the Mediterranean basin, Quercus ilex and Pinus halepensis. Plants were sprayed with the following individual N forms at 40mM N: 15N-nitrate (NO3−), 15N-ammonium (NH4+), 15N-urea or 13C and 15N dual-labeled glycine. Cuticular conductance was used as a surrogate of cuticle permeability to water. Q. ilex had higher N foliar absorption than P. hapelensis. Neither cuticular conductance nor shoot surface area explained N differences in absorption rate between species, which were instead likely linked to differences in stomatal density and presence of trichomes. In both species, foliar N absorption rate and N recovery differed among N forms: urea>NH4+≥glycine≥NO3−. Differences in N absorption rate among N forms were correlated with their physico-chemical properties. The strong positive relationship between 15N and 13C uptake together with detection in shoots of intact dual-labeled glycine (measured by gas chromatography–mass spectrometry), indicated that a significant fraction of glycine was absorbed intact by the seedlings. In both species, higher cuticular conductance was related to faster N absorption from all forms except NO3−. Cuticular conductance had a stronger effect on N absorption from urea and NH4+ than N absorption from glycine, and the effects were more intense in Q. ilex than in P. halepensis. This suggests that variations in cuticle permeability in both species are determined by different mechanisms and that each N form was differently affected. Absorbed N was rapidly translocated to roots, with a larger proportion of N from organic forms being translocated than N from inorganic forms. Foliar fertilization increased plant N content, especially in urea fertilized plants, but direct foliar absorption only explained up to 10% of N content increase. This study demonstrates that two important Mediterranean forest tree species can absorb through their leaves both, inorganic and organic N forms. This has important ecological and applied implications, because all chemical forms of N are present in natural N deposition. Also results show that foliar N fertilization can play an important role for seedling N nutrition, and that the effect will have different impacts depending on the species.
Keywords: Ammonium-nitrate; Cuticular conductance; Glycine; Pinus halepensis; Quercus ilex; Urea

Nitrogen form and concentration interact to affect the performance of two ecologically distinct Mediterranean forest trees - Uscola, Mercedes; Oliet, JuanA.; Villar-Salvador, Pedro; Díaz-Pinés, Eugenio; Jacobs, DouglassF. (European Journal of Forest Research, 2014)
Most studies examining inorganic N form effects on growth and nutrition of forest trees have been conducted on single species from boreal or temperate environments, while comparative studies with species from other biomes are scarce. We evaluated the response of two Mediterranean trees of contrasting ecology, Quercus ilex L. and Pinus halepensis Mill., to cultivation with distinct inorganic N forms. Seedlings were fertilized with different NH4 (+)/NO3 (-) proportion at either 1 or 10 mM N. In both species, N forms had small effects at low N concentration, but at high N concentration they markedly affected the plant performance. A greater proportion of NH4 (+) in the fertilizer at high N caused toxicity as it reduced growth and caused seedling death, with the effect being greater in Q. ilex than in P. halepensis. An increase in the proportion of NO3 (-) at high N strongly enhanced growth relative to low N plants in P. halepensis but had minor effects in Q. ilex. Relatively more NH4 (+) in the fertilizer enhanced plant P concentration but reduced K concentration in both species, while the opposite effect occurred with NO3 (-), and these effects were enhanced under high N concentration. We conclude that species responses to inorganic N forms were related to their ecology. P. halepensis, a pioneer tree, had improved performance with NO3 (-) at high N concentration and showed strong plasticity to changes in N supply. Q. ilex, a late successional tree, had low responsiveness to N form or concentration.
Keywords: ammonium; ecophysiology; Growth; nitrate; Pinus halepensis; Quercus ilex